2004
DOI: 10.1099/vir.0.80131-0
|View full text |Cite
|
Sign up to set email alerts
|

Human CD8+ T cell responses against five newly identified respiratory syncytial virus-derived epitopes

Abstract: CD8+ T lymphocytes play a major role in the clearance of respiratory syncytial virus (RSV)infections. To be able to study the primary CTL response in RSV-infected children, epitopes presented by a set of commonly used HLA alleles (HLA-A1, -A3, -B44 and -B51) were searched for. Five epitopes were characterized derived from the matrix (M), non-structural (NS2) and second matrix (M2) proteins of RSV. All epitopes were shown to be processed and presented by RSV-infected antigen-presenting cells. HLA-A1 tetramers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 28 publications
4
53
1
Order By: Relevance
“…This finding illustrates the well-documented inhibitory effect of RSV infection on T cell proliferation (28,36,(43)(44)(45)(46). Using expanded virus-specific CD8 + T cell populations, we found similar IFN-g responses induced by HLA class I molecules on both virus-infected APCs and peptideloaded APCs.…”
Section: As Enhances In Vitro-induced Rsv-specific Ifn-g Responses Ansupporting
confidence: 82%
See 3 more Smart Citations
“…This finding illustrates the well-documented inhibitory effect of RSV infection on T cell proliferation (28,36,(43)(44)(45)(46). Using expanded virus-specific CD8 + T cell populations, we found similar IFN-g responses induced by HLA class I molecules on both virus-infected APCs and peptideloaded APCs.…”
Section: As Enhances In Vitro-induced Rsv-specific Ifn-g Responses Ansupporting
confidence: 82%
“…In earlier work, we and others have shown that RSV-specific memory CD8 + T cells are present in adult PBMCs, although responses against single epitopes were low and, in most donors, not detectable without in vitro expansion (36)(37)(38)(39)(40)(41)(42). However, the virus-specific T cell response might be directed against a broad panel of HLA-presented peptides derived from the viral proteome (36,39).…”
Section: As Enhances In Vitro-induced Rsv-specific Ifn-g Responses Anmentioning
confidence: 95%
See 2 more Smart Citations
“…With the introduction of HLA class I tetrameric complexes a method of direct detection of virus-specific cells was introduced. The recent characterization by our group (24) and others (23,(25)(26)(27) of several dominant RSV T cell epitopes provided the necessary tools to study the role of CD8 ϩ T cells during RSV infection. In the present study, we describe our investigation into the dynamics and function of the primary CD8 ϩ T cell response in the airways and peripheral blood during a localized severe primary respiratory infection.…”
Section: R Espiratory Syncytial Virus (Rsv)mentioning
confidence: 99%